HOW MANY PAIN PILLS DO WE PRESCRIBE: A SURVEY OF PARTICIPANTS IN SCORE: A QUALITY IMPROVEMENT INITIATIVE (204). Issue 10 (31st October 2021) - Halloran, Kenny; Ellis, Henry; Wilson, Philip; Beck, Jennifer; Schmale, Gregory; Latz, Kevin; Fabricant, Peter; Schmitz, Matthew; Niu, Emily; Heyworth, Benton; Bowen, Richard; Parikh, Shital; et al.
Objectives: The public health opioid abuse epidemic has led to nationwide interest in judicious use and close monitoring of opioid pain medication. Knee arthroscopy(KA) and anterior cruciate ligament reconstruction(ACLR) are common procedures in adolescent patients for which narcotics have been historically utilized for post-operative pain management. The purpose of this study is to investigate pain management strategies following basic KA or ACLR by pediatric sports surgeons who contribute to a multi-center quality improvement initiative(SCORE). Methods: Surgeon participants in SCORE represent fifteen U.S. institutions from primarily academic teaching hospitals who specialize in pediatric sports medicine. Surgeons contribute all ACLR and other KA-related cases. A RedCap survey was distributed to all SCORE surgeon participants in December 2019. A KA (defined as a knee arthroscopy that does not include a ligament reconstruction or a cartilage procedure other than chondroplasty) represented a less invasive procedure, while the ACLR represented a more invasive procedure. Survey results were collected and analyzed for both practice patterns of regional anesthesia utilization and post-operative narcotic prescribing volumes. Results: Twenty-eight SCORE surgeon participants completed the survey, a 100% response rate. A planned prescription of a mean of 16.4 pain pills (range 0-40 pills) were reported for pain management following a KA, only 32.1% of surgeons reported adjunctive regional anesthesia techniques for this procedure in addition to general anesthesia. Following an ACLR, surgeons reported a planned prescription of a mean 23.8 pain pills (range 0-40 pills) and most (92.3%) reported utilization of regional anesthesia for their peri-operative analgesia strategy. Of those using adjunctive regional anesthesia, significant variability was reported: 30.7% reported indwelling catheter placement for peripheral nerve block following ACLR as opposed to a single shot injection method, and several block locations were reported to be utilized of which adductor canal (67.9%) block was the most common (see Figure 1). For both procedure types, variability in multi-modal pain management was noted, with incomplete adoption of the use of additional non-narcotic medication (acetaminophen, 64.2%; and NSAIDS, 75%). Cryotherapy devices were applied/prescribed in 75.0% of knee arthroscopy procedures and 92.8% of ACLR. Conclusions: Despite evidence for effective adjunctive pain management strategies, incomplete adoption of multi-modal techniques and reliance on narcotic medication remains a significant component of pediatric sports surgical practice; with on average > 15 pills prescribed following these procedures. Opportunities for reducing practice variability, adoption of multi-modal analgesia strategies, and decreasing post-operative narcotic use following common adolescent knee procedures exist for this subset of pediatric sports medicine specialists